THE EFFECTIVENESS OF EDUCATIONAL VIDEOS ON LACTATION MASSAGE VERSUS PRINTED BROCHURES ON HUSBANDS' KNOWLEDGE AND SUPPORT IN SUCCESSFUL BREASTFEEDING - Lismaya Puspita Dewi; Teni Nurlatifah HR; Suparni Suparni; Ma'mun Sutisna; Udin Sabarudin; Hidayat Wijayanegara (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
The exclusive breastfeeding program represents a strategic government effort to strengthen the quality of human resources. One effective non-pharmacological approach to addressing this issue is lactation massage, which stimulates milk production and supports the breastfeeding process. This study aimed to evaluate the effectiveness of lactation massage educational videos compared with printed leaflets in improving husbands’ knowledge and roles in supporting successful breastfeeding at the Ciangsana Bogor Independent Midwife Practice in 2025. A quantitative approach with a quasi-experimental design was employed. The study involved 74 husbands of postpartum breastfeeding mothers who accompanied their wives during February–March 2025. Husbands’ knowledge and roles were assessed using structured questionnaires administered prior to the intervention and seven days afterward. Data were analyzed using a paired sample t-test, while the level of effectiveness was determined through gain score analysis. The findings revealed significant differences in both knowledge and roles between husbands who received lactation massage educational videos and those who received printed leaflets. The effectiveness analysis demonstrated that educational videos produced greater improvements, with a 57% increase in knowledge and a 56% increase in husbands’ roles, both classified as moderately effective. In conclusion, lactation massage educational videos are more effective than printed leaflets in strengthening husbands’ knowledge and roles in supporting breastfeeding success. The use of engaging and visually rich educational media may serve as a valuable strategy to foster meaningful husband participation and promote optimal breastfeeding outcomes.